Pedagogia do Oprimido - Pereira, Patrik Sudário de Souza; Salomão, Maria Aparecida Vieira (Revista Hipótese, 2016)
Resenha do Livro FREIRE, Paulo. Pedagogia do Oprimido. Rio de Janeiro: Paz e Terra, 2011. 50ª edição.